2016
DOI: 10.4028/www.scientific.net/kem.702.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nd<sup>3+</sup> Ion on Bismuth Borosilicate Glass Properties

Abstract: This paper reports neodymium doped bismuth borosilicate glasses in composition (40-x)B2O3-40Bi2O3-20SiO2-xNd2O3 where x = 0, 0.5, 1.0, 1.5, 2.0 and 2.5 mol%, have been prepared by melt quenching technique and are characterized through physical properties structural properties, optical absorption spectra and emission spectra measurements. The density is found to increase with the increase in concentration of Nd2O3. The molar volumes of glass decrease where concentration of Nd2O3 where concentration of Nd2O3 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…From the analysis of the NPs absorption spectra near the edge of the ZnO fundamental absorption band (about 375 nm), it can be concluded that the additional laser irradiation does not significantly change the bandgap of the sample but can improve the quality of the crystal lattice, exhibiting a sharper absorption edge near 375 nm. Besides the absorption band of ZnO, several additional absorption peaks were found in the spectra, that can be attributed to the transitions of neodymium ion from the 4 I 9/2 ground state to the following excited levels: 2 K 13/2 + 4 G 9/2 , (at 512 nm), 4 I 9/2 → 4 G 7/2 + 4 G 9/2 + 2 K 13/2 (522 nm), 4 I 9/2 → 4 G 5/2 + 2 G 7/2 (575 nm), 4 I 9/2 → 4 F 7/2 + 4 S 3/2 (740 nm) and 4 I 9/2 → 4 F 5/2 + 2 H 9/2 (794 nm) ( Figure 4 a) [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the analysis of the NPs absorption spectra near the edge of the ZnO fundamental absorption band (about 375 nm), it can be concluded that the additional laser irradiation does not significantly change the bandgap of the sample but can improve the quality of the crystal lattice, exhibiting a sharper absorption edge near 375 nm. Besides the absorption band of ZnO, several additional absorption peaks were found in the spectra, that can be attributed to the transitions of neodymium ion from the 4 I 9/2 ground state to the following excited levels: 2 K 13/2 + 4 G 9/2 , (at 512 nm), 4 I 9/2 → 4 G 7/2 + 4 G 9/2 + 2 K 13/2 (522 nm), 4 I 9/2 → 4 G 5/2 + 2 G 7/2 (575 nm), 4 I 9/2 → 4 F 7/2 + 4 S 3/2 (740 nm) and 4 I 9/2 → 4 F 5/2 + 2 H 9/2 (794 nm) ( Figure 4 a) [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%